Failures in Protein Clearance Partly Underlie Late Onset Neurodegenerative Diseases and Link Pathology to Genetic Risk - Hardy, John (Frontiers in Neuroscience, 2019)
As we identify the loci involved in late onset neurodegenerative disease, we are finding that the majority of them are involved in damage response processes. In this short review, I propose that it is partly a failure in these damage response processes which underlie late onset disease and that the resultant pathology is a marker of the type of damage response which has failed: microglial clearance of damaged neuronal membranes in Alzheimer’s disease (AD), ubiquitin proteasome clearance in the tauopathies, and lysosomal clearance in Parkinson’s disease (PD). In this review, I outline this relationship. This article is not intended as a comprehensive review of the cell biology of any of these disorders but rather a summary of the evidence that the genetics and pathology of these disorders appear to point, in each case, to the removal of misfolded proteins as a critical process in disease pathogenesis.